The Wizard of Oz - "Bau, L.Frank" (Oxford University Press:, Oxford, 2000)
Dorothy lives in Kansas, but one day a cyclone blows her and her house to a strange country called Oz. There, Dorothy makes friends with the Scarecrow, the Tin Man, and the Cowardly Lion. But she wants to go home to Kansas. Only one person can help her, and that's the country's famous Wizard. So Dorothy and her friends take the yellow brick road to the Emerald City, to find the Wizard of Oz
Keywords: Fantasy fiction